The spread in time and space of COVID-19 pandemic waves: the Italian experience from mortality data analyses - del Re, Daniele; Palla, Luigi; Meridiani, Paolo; Soffi, Livia; Loiudice, Michele Tancredi; Antinozzi, Martina; Cattaruzza, Maria Sofia (Frontiers in Public Health, 2024)
Italy was the first European Country affected by COVID-19. Thanks to governmental containment measures (9 March 2020), the spread of COVID-19 was limited. In this context, accurate data assessment is crucial and mortality is a more reliable indicator of the virus spread compared to positive cases count. This study aimed to retrospectively evaluate the impact of the pandemic in different areas of Italy using the time series analysis of official deaths and excess of COVID-19 deaths. Mortality data (23 February- 30 April 2022) by Istituto Nazionale di Statistica were analyzed, including four waves of COVID-19. Previous mortality data (January 2015-November 2019) were used to estimate a Poisson regression model of pre-pandemic mortality pattern and derive the excess of COVID-19 death as the difference between the actual deaths number and the extrapolation of the previous mortality pattern to the pandemic period, separately for Northern, Central, Southern Italy, to compare the impact of mortality across time periods and geographical areas. Estimated excess compared with official COVID-19 mortality shows that during the first wave there was an underestimation of deaths. COVID-19 mortality rate almost doubled the official rate in the North (1.60‰ vs 0.86‰) and nearly tripled it in the South (0.22‰ vs 0.08‰). In late 2020-early 2021, official and estimated mortality curves are closer, displaying just a small gap at the start of second wave. During the fourth wave (end of 2021-early 2022) Northern and Central Italy show agreement; South presents a large relative underestimation of deaths (+90%), with a large increase of excess deaths national quota, 9% 1st wave to 42% 4th wave. The results provide a measure of the COVID-19 excess deaths, and an unbiased estimate of Italian mortality rates. In the first wave, the gap between official COVID-19 and excess mortality was high and lockdown measures may have reduced the spread of the infection. In the fourth wave, the gap for the South increases, probably because the healthcare system may not have coped with the prolonged pressure of pandemic, or for a decreased compliance with official mortality surveillance system that could be overcome in the future digitalizing the process.